Synthesis and Characterization of PDEAEMA-Based Magneto-Nanogels: Preliminary Results on the Biocompatibility with Cells of Human Peripheral Blood - Pikabea, A.; Ramos, J.; Papachristos, N.; Stamopoulos, D.; Forcada, J. (JOURNAL OF POLYMER SCIENCE PART A-POLYMER CHEMISTRY, 2016)
Nanogels based on biocompatible, dual pH- and temperature-sensitive poly(2-(diethylamino)ethyl) methacrylate (PDEAEMA) have been successfully used as nanocontainers for the encapsulation of magnetite, Fe3O4 magnetic nanoparticles (MNPs). For this purpose, citric acid-coated MNPs were encapsulated into previously synthesized PDEAEMA-based nanogels using a poly(ethyleneglycol)-based stabilizer. After the encapsulation of the magnetite MNPs, the so-called magneto-nanogels (MNGs) were proved to be multiresponsive on temperature, pH, and magnetic field and colloidally stable. Moreover, preliminary studies on the biocompatibility of these MNGs with cells of human peripheral blood were performed and evidenced quite tolerable biocompatibility, thus suggesting potential use in biomedical applications. (C) 2015 Wiley Periodicals, Inc.